DATA COMMUNICATION MODEL WITH TECHNOLOGY LORA MULTI-HOP: FIRE INFORMATION CASE STUDY MULTI-STOREY BUILDING - Fitri, Fitri; Marpaung, Jannus; Tjahjamooniarsih, Neilcy (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
LoRa is a long-range communication technology with the advantage of wide coverage but faces challenges in single-hop communication. This issue arises because the communication occurs in Non-Line of Sight (NLOS) conditions. The method used to address this is by testing a multi-hop LoRa communication system, where relays act as intermediaries between the transmitter and the gateway. The results from this study show that communication between the transmitter and relay 1 maintains a consistent RSSI of -94 dBm with an SNR ranging from 8.25 dB to 10 dB. Communication between relay 1 and relay 2 has an RSSI ranging from -83 dBm to -86 dBm and an SNR between 7.50 dB and 9.50 dB. For communication between relay 2 and relay 3, RSSI ranges from -105 dBm to -116 dBm with an SNR between 3 dB and -8 dB. Communication between relay 3 and the gateway shows an RSSI between -94 dBm and -97 dBm with an SNR between 2.00 dB and 2.50 dB. The multi-hop LoRa system successfully detected and transmitted fire data in real-time, including smoke concentrations rising to 85 ppm, with smoke and fire indicators both showing a value of 1, indicating the presence of a fire, as well as changes in temperature and humidity. The system consistently detected and transmitted fire data accurately under various conditions, with sensor data from the transmitter reaching the gateway without loss or damage.